Estrategias metodológicas para potenciar la macrodestreza de hablar en la asignatura de lengua y literatura, en los estudiantes de primer curso de bachillerato general unificado del colegio Beatriz Cueva de Ayora de la ciudad de Loja. Periodo académico 2014-2015 - Condolo Sánchez, Maritza del Cisne (2016)
To develop the research work entitled: STRATEGIES TO PROMOTE METHODOLOGICAL MACRODESTREZA TALKING IN THE COURSE OF LANGUAGE AND LITERATURE IN FIRST YEAR STUDENTS OF GENERAL UNIFIED SCHOOL BACHELOR BEATRIZ AYORA CAVE CITY OF LOJA. 2014-2015 academic year, was raised as a general objective, explain the importance of constructivist methodological strategies to enhance macrodestreza speaking in the subject of Language and Literature. The methods used were:. Scientific, inductive and deductive, each applied in its field of synthetic-analytical study The main techniques used in the development of the thesis were, the survey and the structured interview; and as instruments were applied, questionnaire and structured interview guide. Among the most significant results of the thesis is synthesized, most students have very little developed the skills for listening and speaking; also it can be evidenced little lexicon as an expression of macrodestreza talking. The main conclusion that can be synthesized in the oral expression of students investigated is not smooth, limiting speaking properly and spontaneously. When they express their personal opinions and they do not spontaneously addressed. To develop listening comprehension is suggested to develop recreational activities based on music, inspirational material educational videos, educational television programs, among others. To enhance the oral expression is necessary for the teacher to work in the classroom with active methodological strategies as dialogues interviews, storytelling, games, recordings of readings, worship vocabulary and jargon, descriptions, oral lessons, drama, among others.